What is "Nonbinary" and What Do I Need to Know? A Primer for Surgeons Providing Chest Surgery for Transgender Patients. (10th July 2018) - Esmonde, Nick; Heston, Aaron; Jedrzejewski, Breanna; Ramly, Elie; Annen, Alvin; Guerriero, Jess; Hansen, Juliana; Berli, Jens
Abstract: Background: Most transgender research focuses on patients who identify within the gender binary of either trans-male or trans-female. This largely omits understanding of the "nonbinary" gender identity as it pertains to surgical care. Objectives: We sought to describe a single-institution experience of chest-affirming procedures performed in nonbinary patients, including patient characteristics, surgical techniques, practice pearls, and outcomes. Methods: This was an observational study of nonbinary patients who underwent "chest-affirming surgery" from 2012 to 2017. Demographic and surgical data were collected. A postoperative questionnaire assessing quality of life and body image outcomes was administered. Results: A total of 458 patients with gender dysphoria underwent chest surgery; 58 (13%) patients were nonbinary. All nonbinary patients indicated female sex was assigned at their birth (100%). The most commonly performed procedure was the double incision technique with nipple grafts (72%), followed by the double incision technique without nipple grafts (19%). On a Likert scale, patients reported improved quality of life (4.88, SD ± 0.34), comfort with exercise (4.07, SD ± 0.98), sex life (4.02, SD ± 0.92), and comfort with physical appearance with (4.97, SD ± 0.18) and without clothes (4.69, SD ± 0.47). Conclusions: Chest surgery for nonbinary patients comprises a considerable proportion of transgender surgery practice, and surgeons who provide affirming care should be familiar with the unique characteristics and treatment options for this population. Level of Evidence: 4: